Farmers’ perception on status of livestock insurance in Surkhet district, Nepal - Nepali, Brinda (Journal of Agriculture and Natural Resources, 2021)
Livestock is an important sector for sustained livelihoods of Nepalese people, particularly for small holder farmers. However, occurrence of any disease or disaster may get livestock as the source of sufferings. Livestock insurance can come up as an effective tool for risk management in livestock sector. This study covers the current status and perception of the farmers on livestock insurance. A total of 45 livestock farmers were selected purposively from three municipalities (15 from each municipality) in Surkhet district as Birendranagar Municipality (Birendranagar, Saldada), Bheriganga Municipality (Maintada) and Lekbeshi Municipality (Lekfarsa, Dasarathpur and Satakhani). Data was collected by face-to-face interview with farmers (45), focus group discussions (2) and key informant survey (4). Mortality, high cost of animal, production loss and price risk were the major risks encountered in the farm. Utilization of their saving and loan reimbursement was preferred by the farmers for capital management. Adoption of insurance among livestock owners was found motivated mainly by cooperatives, friends and family. Among twenty insurance companies offering insurance policies in Surkhet district, Everest Insurance Company Limited was popular. Only few farmers were found having complete awareness on livestock insurance. Majority of farmers agreed on insurance as an effective tool for risk management whereas only 64.44% of total respondent farmers were insuring their livestock, out of which 37.93 % had renewed their insurance package. Goats were mostly insured. This study indicates that better coverage, further process simplification, and perspicuity of livestock insurance scheme including awareness raising are essential for livestock insurance to approach higher level of insurance adopters.